Financial stability and economic development : the Barbados experience - Worrell, DeLisle ([s.n.] [S.l.], 1993)
Examines the three most troublesome cases the Central Bank of Barbados has had to deal with. Focuses on the role of finance in development and the responsibilities of the central bank in a liberalised financial system.